FAMILY SPHAEROCERIDAE - Tepedino, Karla P. (Zootaxa, 2016)
This catalog compiles information on the 13 genera and 25 species of Sphaeroceridae that have been reported for Colombia. It is entirely based on literature data and no new records are presented.